Daerah Pemilihan Dewan Perwakilan Rakyat Daerah Kota Pasuruan pada Pemilihan Umum Tahun 2019 - Deshinta Christy Amalia (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This paper aims to explain, examine, and evaluate boundary delimitation of Pasuran City district house representative by the Pasuruan City General Election Commission (KPU) in the 2019 General Election according to Law Number 7 of 2017 concerning Elections as an effort to ensure the implementation of the formation of electoral districts in democracy principle. This study uses a descriptive approach to produce data in the form of words and numbers in a detailed and accurate explanation of the causes of something happening. The object of this research is the General Election Commission (KPU) of Pasuruan City as an election management agency that determines election policy at the Pasuruan City level. The results of the study found that even though there was a gap in seat allocation, the arrangement of the Pasuruan City electoral district house representative in the 2019 Election was in accordance with the principles of electoral district arrangement as stated in the General Election Law and Electoral Comission Republic Indonesia technical guidelines.